Change of 2H/1H Ratio and Adaptive Potential in Living Systems under Formation of Isotope Gradient - S.S. Dzhimak; L.V. Fedulova; A.V.Moiseev; А.А.Basov (Journal of Pharmacy and Nutrition Sciences, 2019)
This article presents data on ability of drinking water with depleted concentrations of deuterium (deuterim depleted water – DDW, ?2H = -762 ‰) to influence on the adaptive capacities and functional activity of rats organism during long period of DDW consumption. The obtained data confirms the favorable effect of reduced ?2H on hepatocytes of medium and shows significant (by 10%) increase of body weight among rats which consumed DDW for 3 weeks after birth. It is also shown that when rats consumed DDW, the non-uniform distribution of deuterium in the blood plasma and liver, kidney and heart tissues is observed. At the same time under natural conditions ?2H was significantly lower in blood plasma than in tissues of internal organs (?2H plasma > ?2H of tissues of internal organs), whereas DDW consumption resulted in more significant decrease of ?2H level in blood plasma than in the internal organs, which phenomena was accompanied by change of direction of 2H/1H isotope gradient: ?2H of plasma < ?2H of tissue of internal organs. Stable change in direction of 2H/1H isotope gradient over 3 weeks is expressed by lower rate of weight gain in the first generation of rats. All these facts can be caused by influence of 2H/1H isotope gradient on long-term adaptation mechanisms, but not on short-term adaptation reactions. Decrease of ?2H in blood plasma and tissues of internal organs increases to a greater extent the resistance of an organism to influence of unfavorable environmental factors among future generations of rats consuming DDW for a long time.